Effect of low-melting-point sintering aid on densification mechanisms of boron carbide during spark plasma sintering. (1st April 2019) - Zhang, Mei; Li, Ruidi; Yuan, Tiechui; Feng, Xiao; Xie, Siyao
Abstract: A densification creep model was proposed to analyze the densification mechanism involved in spark plasma sintering (SPS) of boron carbide containing low-melting-point sintering aid. This model incorporated the effect of the sintering aid on relative density as well as the actual internal stress during SPS of boron carbide ceramics. The internal stress bias caused by sintering aid was considered and a more accurate effective stress was used to investigate the kinetics during SPS. The proposed model explains why an increase of sintering aid amount decreases the sintering activation energy and promotes densification. Graphical abstract: Unlabelled Image